KOMPETENSI PROFESIONAL GURU, MOTIVASI BELAJAR, DAN GAYA BELAJAR BERPENGARUH TERHADAP PEMAHAMAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 1 GONDANG, NGANJUK - Andriani, Dwi Nila (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The aims of this research are for Analyzing the influence of professional teacher competence, learning motivation, and learning styles of students for economic understanding of eleventh grades student of SMA Negeri 1 Gondang, Nganjuk. In this research, writer uses quantitative methods as a research methodology. Population in this research are eleventh grades students in SMA Negeri 1 Gondang who are 112 students. Writer uses Simple Random Sampling as a Research technique which consists of 88 samples. Result of this research shows There is 77, 3% significance between professional teacher competence, students learning motivation, students learning styles and economic understanding of students